1994
DOI: 10.1002/1097-0142(19941015)74:8<2261::aid-cncr2820740809>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Base of skull chordoma. A correlative study of histologic and clinical features of 62 cases

Abstract: Background. Chordomas are uncommon primary malignant tumors of bone that typically occur in the axial skeleton including the sacrum, vertebrae, and skull base. The base of skull tumors usually are not amenable to complete surgical resection, and most require postoperative radiotherapy. The natural history of skull base chordoma is typified by slow locally invasive tumor progression and eventual death, although few parameters are known that allow stratification of patients into prognostic groups. Methods. Sixty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(101 citation statements)
references
References 21 publications
4
93
4
Order By: Relevance
“…We observed a 7:2 ratio in favor of males. Although sex is not thought to be of prognostic value in chordomas, it has been suggested that female sex is an independent predictor of shortened survival in skull base chordomas (20). We in our series did not notice such a finding.…”
Section: Histopathological/cytological Characteristicscontrasting
confidence: 76%
See 1 more Smart Citation
“…We observed a 7:2 ratio in favor of males. Although sex is not thought to be of prognostic value in chordomas, it has been suggested that female sex is an independent predictor of shortened survival in skull base chordomas (20). We in our series did not notice such a finding.…”
Section: Histopathological/cytological Characteristicscontrasting
confidence: 76%
“…Tumors of the clivus are best managed by subtotal decompression and radiotherapy. These present a major challenge to the neurosurgeon because gross total removal of the tumor with preservation of neural and vascular structures is difficult (20). High cervical tumors can be managed by trans-oral decompression and posterior stabilization of the spine (2).…”
mentioning
confidence: 99%
“…10 However, O'Connell et al 11 reported that female sex was an independent predictors of shorter survival (P ¼ 0.004) for skull base chordoma. The same observation was reported by Thieblemont et al 12 in a series of 26 patients with chordoma.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor size and radiation dose appear to be inverse and direct, respectively, predictors of tumor control. 5,43,72,95 Other factors such as sex (female sex being associated with a poorer prognosis), 5,40,72 involvement of dose-limiting structures, patient age, primary compared with recurrent disease, 30 and pathological features are also currently being studied. Prognostic factors, once firmly established, may assist the clinician in formulating therapeutic decisions.…”
Section: Neurosurgical Focus / Volume 10 / March 2001mentioning
confidence: 99%